THE INFLUENCE OF LEARNING STYLES AND MOTIVATION OF CLASS XI STUDENTS ON THE EFFECTIVENESS OF DIFFERENTIATED GEOGRAPHY LEARNING AT SMA NEGERI 3 HALMAHERA UTARA, INDONESIA - Elvis Awa; Roni Alim Ba'diya Kusufa; Ninik Indawati; Dwi Fauzia Putra (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2026)
This study analyzes the influence of students’ learning styles and learning motivation on the effectiveness of differentiated Geography learning at SMA Negeri 3 Halmahera Utara. This study is based on the importance of differentiated learning in accommodating students’ learning characteristics in the context of an archipelago with diverse geographical conditions. A quantitative approach with an explanatory method was used involving 61 students. Data were collected through a closed questionnaire through validity and reliability tests. Data analysis used a t-test. The results showed that learning styles have a significant influence on the effectiveness of differentiated learning, with a t-value of 10.786 and a learning motivation t-value of 7.228, with a coefficient of determination of 47.0%. These findings confirm that differentiated learning based on student characteristics and local environmental conditions increases student engagement, learning effectiveness, and contextual relevance in Geography education. Keywords: Learning Styles, Learning Motivation, Differentiated Instruction